Performance Analysis of a Gold extraction process system under Different Failure using Boolean algebra - Chandra, A; Gupta, S (International Journal of Computer Sciences and Engineering, 2025)
This paper deals with the ensuring reliability and Availability of Gold extraction system is extremely complex and extends to all the stages of the service life of a system. The gold extraction system analyze a system with two type of failure. The rate of failure is exponential .The system resolved by Boolean algebra. Several measures of availability and MTTF of system are obtained .Some numerical examples, along with graph have been appended at the end to highlight the importance of the result.